Design and control of electrotechnological systems: A multi-objective optimization approach. Issue 1 (7th January 2020) - Pleshivtseva, Yuliya; Rapoport, Edgar; Nacke, Bernard; Nikanorov, Alexander; Di Barba, Paolo; Forzan, Michele; Sieni, Elisabetta; Lupi, Sergio
Abstract : Purpose: This paper aims to investigate different multi-objective optimization (MOO) approaches for design and control of electromagnetic devices. The main goal of MOO is to find the set of design variables or control parameters which will provide the best possible values of typical conflicting objective functions. Design/methodology/approach: In the research studies, standard genetic algorithm (GA), non-dominated sorting GA (NSGA-II), migration NSGA algorithm and alternance method of optimal control theory are discussed and compared. Findings: The test practical problems of multi-criteria optimization of induction heating processes with respect to chosen quality criteria confirm the effectiveness of application of considered MOO approaches both for the problems of design and control. Originality/value: This paper represents and investigates different MOO approaches for design and control of electrotechnological systems.